TAX AGGRESSIVENESS REVIEWED FROM LIQUIDITY, LEVERAGE, AND PROFITABILITY MODERATED BY INDEPENDENT COMMISSIONERS - Miranda, Miranda Septy Andini; Shelly Prahadian Putri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2025)
This study aims to determine the effect of liquidity, leverage, and profitability on tax aggressiveness, which is moderated by independent commissioners. The population and sample consisted of all 13 Islamic Commercial Banks (Bank Umum Syariah/BUS) in Indonesia, with an observation period from 2020 to 2024 (5 years). The analysis technique used was Moderated Regression Analysis (MRA), processed using the STATA application, with hypothesis testing conducted using the t-test and F-test. Partially, only leverage has a significant influence on tax aggressiveness. Liquidity, profitability, and independent commissioners individually do not show a significant effect. Simultaneously, all independent variables (liquidity, leverage, profitability) along with the independent commissioner variable do significantly influence tax aggressiveness. The independent commissioner variable is not able to moderate the effect of liquidity and leverage on tax aggressiveness, but it is able to moderate the effect of profitability on tax aggressiveness. The conclusion is that, partially, only leverage affects tax aggressiveness, while liquidity, profitability, and independent commissioners do not. However, simultaneously, the four variables (liquidity, leverage, profitability, and independent commissioners) are proven to significantly influence tax aggressiveness. Furthermore, the independent commissioner is only capable of moderating the relationship between profitability and tax aggressiveness, and fails to moderate the influence of liquidity and leverage